Implemetasi Sistem Pendukung Keputusan Pemberian Beasiswa Menggunakan Metode MABAC Pada STIKES Keluarga Bunda Jambi - Mawaddatarrohmah; Setiawan Assegaff; Nurhadi (LPPM Universitas Dinamika Bangsa, 2025)
STIKES Keluarga Bunda Jambi is one of the campuses located in the Jambi area for the decision to award scholarships is still ineffective because data processing takes a relatively long time to determine who is entitled to receive scholarships and in recording student data there are often errors in inputting student identities. Therefore, this study aims to provide a solution to the problem that occurs by offering a scholarship decision support system using PHP programming language and MySQL DBMS where the author develops the system with the waterfall method and uses a unified model language system model approach using use case diagrams, activity diagrams, class diagrams and flowchart documents. The new system produces outputs that can display student data, admin data, criteria data, sub-criteria data, student assessment data and The results of the calculation are enough to make it easier to provide scholarships using the MABAC (Multi-Attributive Border Approximation Area Comparison)